ANALYTICAL STUDY OF QUOTATIONS IN MOHAMMAD DAOUDIA’S JOURNALISTIC WRITINGS - Omar Hazaymeh (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
Language is a means of communication and knowledge that individuals utilize to express their desires and share their cultural innovations through various disciplines. In order to enrich their writing, authors rely on a multitude contemporary and former sources, including linguistic and historical citations and quotations texts. The present study aims at examining the quotations in Mohammad Daoudia’s newspaper articles. The study's data were comprised of articles authored by Daoudia and published on Jordanian news websites in January 2022. The findings showed that the writer quoted directly and indirectly from a wide range of historical, religious, poetic, prose, and official sources. Additionally, the results demonstrated that the writer used these quotations in various ways and for functions.